Problem Solving Profile of Students with High Self-Efficacy Levels in terms of Gender - Putri, Reni Kurnia; Hariyanti, Firda (JME (Journal of Mathematics Education), 2022)
This research is motivated by the low mathematical problem-solving ability of MTs students. The purpose of the study was to describe the problem-solving profile of students with high self-efficacy in terms of students' gender. The research method is qualitative research, where the research subject consists of one male student and one female student with a high level of self-efficacy from MTs students in class VIII-A. The main instrument is the researcher himself, supported by problem-solving tests, self-efficacy questionnaires, and interview guidelines. The data analysis technique was carried out using stages, namely: data reduction, data presentation, and conclusion. The results showed that in solving problems male students with high self-efficacy were superior to female students with high self-efficacy, namely: (1) In The stage of understanding the problem, male and female students with high self-efficacy were able to name all that information known and asked. (2) In the planning stage, male and female students with high self-efficacy are good enough in determining strategies. (3) In the stage of implementing the plan, male and female students with high self-efficacy were following the planned strategy. However, in practice, female students with high self-efficacy make many mistakes, so the results obtained are not correct. (4) In the re-examination stage, male and female students with high self-efficacy re-examine the results of their answers.